Regional Maritime Cooperation in Maintaining Maritime Security and Stability: A Test Case for ASEAN Unity and Centrality - Damayanti, Angel (Centre for Business and Diplomatic Studies (CBDS) Bina Nusantara University, 2017)
Southeast and East Asia region has emerged as a global strategic maritime. Yet, maritime in the region remains vulnerable with overlapping claims on sea borders, piracy attacks and other transnational challenges at sea. For these purposes, some major powers in the region such as the US, China and Indonesia have launched their respective strategies in securing maritime for their interests. To harmonize the various interests, ASEAN with its counterparts in East Asia region need an ASEAN-led, inclusive and comprehensive regional maritime mechanism and strategic partnership between ASEAN member states and its dialog partners to maintain good order at sea. In November 2015, the East Asian Summit eventually launched a joint statement on Enhancing Regional Maritime Cooperation to justify the centrality of ASEAN and to counter the failure of ASEAN Defense Minister Meeting. In such case, ASEAN member states need to manage their disunity to minimize hindrances of the realization and implementation of the plan. This paper mainly elaborates the reasons why the region needs regional maritime cooperation and challenges that ASEAN have to deal with in order to implement the ASEAN unity and centrality in promoting maritime cooperation and regional stability. To explain the maritime strategies of ASEAN and its dialogue partners, this study uses qualitative methods and utilizes statesâ€™ documents as well as ASEAN statements particularly on maritime issues.Â Â